Mitochondrial Heat Shock Protein Machinery Hsp70/Hsp40 Is Indispensable for Proper Mitochondrial DNA Maintenance and Replication - Jiří Týč (American Society for Microbiology, 2015)
ABSTRACT  Mitochondrial chaperones have multiple functions that are essential for proper functioning of mitochondria. In the human-pathogenic protist Trypanosoma brucei, we demonstrate a novel function of the highly conserved machinery composed of mitochondrial heat shock proteins 70 and 40 (mtHsp70/mtHsp40) and the ATP exchange factor Mge1. The mitochondrial DNA of T. brucei, also known as kinetoplast DNA (kDNA), is represented by a single catenated network composed of thousands of minicircles and dozens of maxicircles packed into an electron-dense kDNA disk. The chaperones mtHsp70 and mtHsp40 and their cofactor Mge1 are uniformly distributed throughout the single mitochondrial network and are all essential for the parasite. Following RNA interference (RNAi)-mediated depletion of each of these proteins, the kDNA network shrinks and eventually disappears. Ultrastructural analysis of cells depleted for mtHsp70 or mtHsp40 revealed that the otherwise compact kDNA network becomes severely compromised, a consequence of decreased maxicircle and minicircle copy numbers. Moreover, we show that the replication of minicircles is impaired, although the lack of these proteins has a bigger impact on the less abundant maxicircles. We provide additional evidence that these chaperones are indispensable for the maintenance and replication of kDNA, in addition to their already known functions in Fe-S cluster synthesis and protein import. IMPORTANCE  Impairment or loss of mitochondrial DNA is associated with mitochondrial dysfunction and a wide range of neural, muscular, and other diseases. We present the first evidence showing that the entire mtHsp70/mtHsp40 machinery plays an important role in mitochondrial DNA replication and maintenance, a function likely retained from prokaryotes. These abundant, ubiquitous, and multifunctional chaperones share phenotypes with enzymes engaged in the initial stages of replication of the mitochondrial DNA in T. brucei.